2015
DOI: 10.3390/vaccines3030490
|View full text |Cite
|
Sign up to set email alerts
|

Interest of Tumor-Specific CD4 T Helper 1 Cells for Therapeutic Anticancer Vaccine

Abstract: Nowadays, immunotherapy represents one promising approach for cancer treatment. Recently, spectacular results of cancer immunotherapy clinical trials have confirmed the crucial role of immune system in cancer regression. Therapeutic cancer vaccine represents one widely used immunotherapy strategy to stimulate tumor specific T cell responses but clinical impact remains disappointing in targeting CD8 T cells. Although CD8 T cells have been initially considered to be the main protagonists, it is now clear that CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 102 publications
0
29
0
Order By: Relevance
“…3 Lessons learnt from previous clinical trials support that future anticancer vaccines should take into account some critical points such as the ability of vaccine to stimulate high quality memory antitumor CD8 T-cell responses, to induce CD4 helper T-cell response and to block immune suppression and/or exhaustion. 4,5,40,41 In our study, we reported the ability of the mTOR inhibitor temsirolimus to highly potentiate anticancer vaccines when combined with T regs blockade in vivo. This effect is mainly driven by the induction of antitumor memory CD8 T cells.…”
Section: Discussionmentioning
confidence: 81%
“…3 Lessons learnt from previous clinical trials support that future anticancer vaccines should take into account some critical points such as the ability of vaccine to stimulate high quality memory antitumor CD8 T-cell responses, to induce CD4 helper T-cell response and to block immune suppression and/or exhaustion. 4,5,40,41 In our study, we reported the ability of the mTOR inhibitor temsirolimus to highly potentiate anticancer vaccines when combined with T regs blockade in vivo. This effect is mainly driven by the induction of antitumor memory CD8 T cells.…”
Section: Discussionmentioning
confidence: 81%
“…We describe that moDCs stimulated by tumor supernatant of the highly cytotoxic NB-PDT condition are able to provide the adequate stimulatory signals for the proliferation of CD4+ T cells (Figure 6a) and differentiation towards Th1 CD4+ effector T cells, as indicated by the substantial release of IFNγ (Figure 6b). Th1 CD4+ effector T cells are known to have a clear antitumor role and, via IFNγ release, can sustain a potent cellular immune response involving CD8+ cytotoxic T cells [40,41]. Although the activation of these cytotoxic T cells was not investigated in our study, their importance for tumor control is evident and we will further expand on this aspect in future in vivo studies.…”
Section: Discussionmentioning
confidence: 92%
“…This correlates with studies where engagement of the T-helper compartment has been shown to increase the efficacy of cancer vaccine strategies. [32][33] Aarntzen and colleagues have demonstrated that combining CD4 and CD8 epitopes improves median progression-free survival of patients with stage III and IV melanoma with detectable antigen-specific responses among skin-infiltrating lymphocytes. 34 Similar approaches featured the production of longer peptides including both CD4 and CD8 epitopes.…”
Section: Discussionmentioning
confidence: 99%